PENGARUH LITERASI KEUANGAN DAN PERILAKU KONSUMTIF MELALUI PENGELOLAAN KEUANGAN TERHADAP KEPUTUSAN INVESTASI PADA GENERASI MILENIAL DI KOTA TENGGARONG - Indra Prasetia, Dwi; Kardinar Wijayanti, Silvana; Akhmadiansyah, Akhmadiansyah (Jurnal GeoEkonomi, 2025)
Indonesia is a country with a large population. Experts predict that Indonesia will experience a significant demographic bonus in the coming decades. This is expected to support the achievement of Indonesia's golden era until 2045. The millennial generation is the second largest population group in Indonesia. With the large population of the millennial generation who have entered productive age, they are the main drivers of the country's economic growth. This study was designed to provide an understanding of the influence of financial literacy and consumptive behavior of the millennial generation in Tenggarong City through financial management on their decisions to invest. This study uses an associative quantitative method. This research process obtained 100 people as respondents. Data collection was carried out by distributing questionnaires, which would then be analyzed using an analysis tool in the form of the PLS-SEM statistical technique. The results of this study indicate that investment decisions are significantly influenced by financial literacy and consumptive behavior. Financial management can also be a significant mediator between financial literacy and consumptive behavior on investment decisions. A significant correlation is also found in the relationship between financial literacy and consumptive behavior. Thus, financial literacy and good financial management can help the millennial generation reduce excessive consumer behavior and improve the quality of their investment decisions.